1999
DOI: 10.1074/jbc.274.6.3253
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4Gene Regulation and Manipulation

Abstract: A decade has passed since the cloning of the insulin-responsive glucose transporter, GLUT4. Numerous studies have demonstrated the complex hormonal and metabolic regulation of GLUT4 gene expression in adipose tissue and muscle. Careful dissection of the regulatory elements in the GLUT4 promoter has provided insight into the intricate control of this central gene of glucose homeostasis. Genetic manipulation of mice has provided further insight into the role of GLUT4 in carbohydrate and lipid metabolism at the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 38 publications
2
90
0
Order By: Relevance
“…As reviewed recently (1,2), there are many hormones or stimuli reported to regulate glucose transport. Insulin stimulation of glucose transport has received considerable study and the signaling pathways involved are understood in more detail than other regulators of glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed recently (1,2), there are many hormones or stimuli reported to regulate glucose transport. Insulin stimulation of glucose transport has received considerable study and the signaling pathways involved are understood in more detail than other regulators of glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…Both insulin and diabetes also exert potent effects on transcription of metabolic and growth-regulatory genes in skeletal muscle, including ras-related associated with diabetes (RAD1), hexokinase 2 (HK2), and glucose transporter type 4 (GLUT4) (18)(19)(20)(21). Basal expression of these genes was significantly reduced in IR-Mut myotubes compared with controls ( Fig.…”
Section: Insulin Signaling Is Defective In Insulin-resistant Ips Cellmentioning
confidence: 99%
“…7A, we found that the levels of GLUT-4 were dramatically increased in Cav-1 null mice, possibly as a response to the postprandial hyperinsulinemia. Other groups have previously reported that GLUT-4 levels are elevated in response to hyperinsulinemia (3,5). Furthermore, a recent report indicates that, in 3T3L1 adipocytes, disruption of caveolae with cholesterol chelating agents results in an insulin-independent increase in plasma membrane GLUT-4 (39).…”
Section: Cav-1 Null Mice Have a Primary Defect In Insulin Signaling Imentioning
confidence: 98%